Account of Structural, Theoretical, and Photovoltaic Properties of ABO3 Oxide Perovskites Photoanode‐Based Dye‐Sensitized Solar Cells. Issue 2 (29th December 2021) - Bhojanaa, K. B.; Soundarya Mary, A.; Shalini Devi, K. S.; Pavithra, N.; Pandikumar, A.
Abstract : In terms of addressing the rapid global energy demand while simultaneously suppressing important environmental issues from an economic aspect, dye‐sensitized solar cell (DSSC) technology has emerged as a most viable option for traditional silicon‐based solar cell technology. In the DSSC, the photoanode takes precedence over other components. There have been numerous reviews of binary oxides‐based photoanodes to date. From the last decade, ternary oxides, particularly ABO3 ‐type perovskites, have gained popularity as DSSC photoanodes. Due to their excellent physiochemical properties, supply of excellent photovoltaic performance, and simple modification method by modifying the atomic composition of their constituents, ABO3 perovskites have firmly established themselves as innovative over the conventional photoanode materials for DSSC. The lack of a review based on ABO3 perovskites limits its further exploration. Furthermore, the theoretical means of a material is a prerequisite to designing efficient photoanode materials for DSSC. Taking these facts into an account, this review will focus on fundamental aspects of ABO3 perovskite materials, theoretical insights, and their potential application as photoanode materials in DSSCs. It is anticipated that this review pool will aid in gaining in‐depth knowledge about ABO3 perovskites by utilizing their experimental, theoretical, and photovoltaic aspects for future advancement. Abstract : Structural and theoretical aspects of ABO3 perovskites along with its photovoltaic performances aid to develop better photoanodes for dye‐sensitized solar cells.